A Novel Signal-Amplified Immunoassay for the Detection of C-Reactive Protein Using HRP-Doped Magnetic Nanoparticles as Labels with the Electrochemical Quartz Crystal Microbalance as a Detector - Ning Gan; Ping Xiong; Ji Wang; Tianhua Li; Futao Hu; Yuting Cao; Lei Zheng (Journal of Analytical Methods in Chemistry)
A novel horseradish peroxidase- (HPR-) doped magnetic core-shell Fe3O4@SiO2@Au nanocomposites (Fe-Au MNPs) were employed on immunoassay for the determination of C-reactive protein (CRP) based on a electrochemical quartz crystal microbalance detector (EQCM). Firstly, the secondary CRP antibody and HRP were both immobilized on the Fe-Au MNPs (Fe-Au MNPs-anti-CRP2/HRP) as a signal tag. Secondly, the above tag and the primary antibody (anti-CRP1) in the bottom of 96-well microtiter plate were employed to conjugate with a serial of CRP concentrations to produce a sandwich immunocomplex. Thirdly, the immunocomplex solution was subsequently exposed to 3,3′-diaminobenzidine (DAB) in the presence of H2O2, resulting in an insoluble product. When the precipitation solution was dripped on EQCM, it can achieve a decrease of frequency of crystal (Δf). The amount of Δf was proportional to (CRP) from 0.003 to 200 ng mL−1 with a low detection limit of 1 pg mL−1. Compared with the enzyme-linked immunosorbent assay (ELISA), the immunoassay shows greatly improved sensitivity due to the significant amount of HRP labeled on signal tag. It also has good specificity and low sample consumption, which is expected to be a benefit for the CRP screening in early diagnosis of cardiovascular disease.